Effect of Training Platform on Interest and Academic Performance in Technical Education among Technical College Students in Ondo-State, Nigeria - Deborah Ahuoiza Vincent (Journal of Digital Learning and Education, 2022)
Training platform is closely associated to e-learning. Training platforms are primarily focused on the delivery of online learning. It serves as a platform for a variety of uses, including asynchronous and synchronous methods of teaching and learning. This study investigated the effect of training platform instruction on students’ interest and academic performance in technical education among technical college students. The study was conducted in Ondo State and applied a quasi-experimental methodology. The study involved 284 participants, including 232 male and 52 female students from two technical colleges in Ondo State. For effective investigation, training technical education interest rating (TEIR) and technical education academic performance (TEAP) instrument were faces verified by 3 experts. To analyze the null hypotheses that served as the study guiding principles and to provide answers to the research questions, the collected data were analyzed using the mean and analysis of variance (ANOVA). The results showed that students’ interest and academic performance are enhanced when technical education is taught using a training platform method than the conventional instructional method. The study also finds a significant variation in the academic performance of the students who were taught technical education via the training platform instructional method. Based on these findings, the study concluded that the training platform instructional approach improves students' academic performance and interest more than the traditional approach in technical education. Also, male students had a stronger interest in technical education than female students who are taught technical education using the training platform instructional approach, and female students in technical institutions outperformed male students academically when utilizing the training platform. The study therefore recommended that technical colleges should take into consideration the use of training platform as an addition to the conventional instructional practices to enhance the quality of learning and teaching.